Proposed marketing strategy for pt. Eka nusa kreasindo to boost sales - Prabowo, Aryo; Furinto, Asnan (The Indonesian Journal of Business Administration, 2018)
Abstract - PT. Eka Nusa Kreasindo is a company engaged in the field of house developer and contractors headquartered in South Jakarta. The focus of the discussion on this journal is Villa Aster Residence. Villa Aster Residence is a housing project with a land area of 27.228m2 which consists of 186 units of houses and 6 units of kiosk. Sales of property, especially housing, experienced a phase of up and down. PT. Eka Nusa Kreasindo is currently experiencing a decline in sales in the period of July 2017 to February 2018. The decline in sales can be caused by many things; from the sluggish purchasing power to the spread of information on online media and offline media that less than the maximum. Dealing with problems faced by PT. Eka Nusa Kreasindo, the authors perform in-depth analysis using Porter 5 Forces and Customer Journey Analysis as a form of external analysis and Business Model Canvas and SWOT as a form of internal analysis. Based on the results of the analysis, the author then creates a new marketing strategy proposal that involves analysis of Porter Generic Strategies and conclude that the company is better focused on low cost strategy. Customer Journey Map analysis results in the company should make a new marketing strategy and corporate strategy which focused on consumers. At last, on Business Canvas Model analysis, the company should make an adjustment by doing integration in marketing activities both on cost plans and implementation of marketing activities.Keyword: business strategy, real estate business, customer journey map